The Effect of Deppamil Dangke to Pregnant Women with Chronic Energy Deficiency on the Outcome of Newborn Babies in Enrekang Regency - Hidayanti Arifuddin; Mardiana Ahmad; Farid Husin; Andi Nilawati Usman; Martira Maddeppungeng; Suryani As'ad (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Chronic energy deficiency (CED) tends to occur in pregnant women and carry detrimental effects, especially on the women during labour and on the fetus. Therefore, it is extremely important to increase nutritional intake during pregnancy for optimized newborn outcome. There are a variety of ways to treat CED, one of which is to provide additional food during pregnancy. This study aims to determine the effect of Deppamil Dangke to pregnant women with CED on the outcome of newborns. This research method used a quasi-experimental design conducted for 18 weeks in Enrekang Regency, with a population of 28 pregnant women > 20 weeks gestation who then used a exhaustive sampling technique where the sample was divided into two consisting of 14 intervention samples and 14 control samples. The results of the study were tested using Mann Whitney showing the value of ρ > α (0.05), which means that there was no difference in the outcome of newborns between the intervention group and the control group. Conclusion. Consuming Deppamil Dangke did not have a direct effect on the outcome of newborns, even though the difference was not significant, but the average outcome of newborns in mothers who consumed Deppamil Dangke + PMT was in the normal category.